Nekatere zgodovinske konstrukcije pravilnega sedemkotnika - Hladnik, Milan (Obzornik za matematiko in fiziko, 2014)
In this short excursion into the history of constructing the regular heptagon we first described two old approaches, one ascribed to Archimedes and the other to Viete. Then we also present another one involving a parabola and finish with a simple modern marked ruler and compass construction.
Keywords: geometrijske konstrukcije; pravilni sedemkotnik; Arhimedova konstrukcija; Johnsonova konstrukcija